Analisis Peran Stakeholder dalam pengembangan Kepulauan Widi - ADI muliadi MULIADI (Journal of Environmental Engineering and Waste Management, 2023)
The Widi Islands have a potential marine ecotourism area of 88.57%, such as pristine, natural and exotic natural beauty, as well as marine biota with high diversity. However, with all that, threats to resources and unfair use of all elements (privatization of the area) in the Widi Islands are still high. One of the threats that has been in the public spotlight so far is the island selling case. Therefore it is very important to identify the roles and authorities of stakeholders for the sustainable development of the Widi Islands. This study uses an empirical paradigm using primary data obtained through FGDs and interviews as well as secondary data from documentation studies which are then analyzed using mactor. The results of the study show that the key actors who have high influence and low dependency are the Ministry of Maritime Affairs and Fisheries (KKP), Non-Governmental Organizations (NGOs), and the private sector. Then actors who have a high level of influence and dependency are the Director General of Marine Spatial Management (DJPRL), Regional Marine Protected Areas Center (BKKPD), Regional Government (PEMDA). Meanwhile, actors with a high level of dependency and little influence are the Maritime Affairs and Fisheries Service (DKP), the Tourism Office (DISPAR), community supervisory groups (POKMASWAS), and fishermen.